TRADE OPENNESS AND MANUFACTURING GROWTH OF ASIAN ECONOMIES: INVESTIGATING LINEAR AND NON-LINEAR EFFECT (Journal of Economics and Sustainability, 2025)
This study investigates the linear and non-linear effects of trade openness on manufacturing growth in 35 selected Asian economies from 2004 to 2022. Using linear and quadratic regression specifications derived from the production function framework of growth, panel data fixed effects models, two-stage least square (2SLS) method, and two-step difference and system generalized method of moments (GMM) estimation techniques, the study uncovers significant findings. The results from the linear static and dynamic specifications indicate a positive and significant impact of trade openness on manufacturing growth. Moreover, factors such as tariff rate, financial development, control of corruption, foreign direct investment, and foreign exchange reserve also play a significant role in influencing manufacturing growth in the Asian economies. The study further reveals that the relationship between trade openness and manufacturing growth is non-linear. While additional trade openness initially has a positive effect on manufacturing value-added growth, beyond a certain threshold, the marginal impact of trade openness becomes negative. This study makes valuable contributions to the existing literature by providing evidence on the linear effect of trade openness on manufacturing growth and by being the first to analyze the optimality or non-linearity of trade openness specifically in the Asian region. The findings suggest that higher levels of trade openness offer opportunities for knowledge sharing, technological advancements, innovation, increased productivity, access to new capital goods, and attraction of foreign investment in the manufacturing sector. However, the study emphasizes the importance of specialization in producing high-quality goods and developing expertise to achieve sustained growth in the manufacturing sector.